SOCIALIZATION OF HEALTHY COOKING TO SUPPORT BUSINESS DEVELOPMENT PRIMA KARYA KATERING IN BRUMBUNGAN VILLAGE DISTRICTS CENTRAL SEMARANG - Christiana, Metta; Nurcahyo, Andi; Muhaimin, Ahmad (Universitas Semarang, 2021)
Katering Prima Karya is one of the small caterers in Brumbungan Village which tastes quite good. Consumers of this catering generally have subscribed for years, and many are over 60 years old. They say it matches the taste of the catering. Many of the menus offered are cooked by frying. Catering owners want to provide a more varied menu of dishes, but unfortunately they do not have adequatecooking utensils. There are many more obstacles faced by this business due to the limited knowledge and abilities of the owner. The number of Prima Karya catering customers who are more than 60 years old, the USM PKM team aims to provide socialization about healthier cookingmethods so that the menu offered can be more varied and healthier.The result achieved is an increase in the knowledge, ability and willingness of the caterer to be able to cook in a more varied and healthier way so that they can provide a more varied and healthier menu for their customers, most of whom are over 60 years old.